2019
DOI: 10.1177/1178224218823511
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on palliative sedation

Abstract: ‘Palliation sedation’ is a widely used term to describe the intentional administration of sedatives to reduce a dying person’s consciousness to relieve intolerable suffering from refractory symptoms. Research studies generally focus on either ‘continuous sedation until death’ or ‘continuous deep sedation’. It is not always clear whether instances of secondary sedation (i.e. caused by specific symptom management) have been excluded. Continuous deep sedation is controversial because it ends a person’s ‘biographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 115 publications
(152 reference statements)
2
91
0
4
Order By: Relevance
“…However, if the intended action is not actually resulting in the relief of suffering, is the action still considered good? His claim is based on his own experiences in providing deep sedation to pediatric patients undergoing procedures where a "nontrivial minority" are able to recall conversations that happened while they were sedated and also report having felt "pain, fear or anxiety without the ability to express their symptoms" during the procedure while under moderate or deep sedation (Kon, 2011, p. 41 (Leboul et al, 2017;Twycross, 2019). For example, Kon (2011) asserts that "it is unquestionable that some patients receiving moderate or deep sedation also suffer and are unable to express their suffering to providers" (p. 41).…”
Section: Doctrine Of Double Effect (Dde)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the intended action is not actually resulting in the relief of suffering, is the action still considered good? His claim is based on his own experiences in providing deep sedation to pediatric patients undergoing procedures where a "nontrivial minority" are able to recall conversations that happened while they were sedated and also report having felt "pain, fear or anxiety without the ability to express their symptoms" during the procedure while under moderate or deep sedation (Kon, 2011, p. 41 (Leboul et al, 2017;Twycross, 2019). For example, Kon (2011) asserts that "it is unquestionable that some patients receiving moderate or deep sedation also suffer and are unable to express their suffering to providers" (p. 41).…”
Section: Doctrine Of Double Effect (Dde)mentioning
confidence: 99%
“…For example, Kon (2011) asserts that "it is unquestionable that some patients receiving moderate or deep sedation also suffer and are unable to express their suffering to providers" (p. 41). His claim is based on his own experiences in providing deep sedation to pediatric patients undergoing procedures where a "nontrivial minority" are able to recall conversations that happened while they were sedated and also report having felt "pain, fear or anxiety without the ability to express their symptoms" during the procedure while under moderate or deep sedation (Kon, 2011, p. 41 (Leboul et al, 2017;Twycross, 2019). It has been suggested that there is limited understanding of the physiological mechanisms that occur in processing pain or distressing symptoms in patients who are unconscious (Carvalho et al, 2011).…”
Section: Doctrine Of Double Effect (Dde)mentioning
confidence: 99%
“…When we talk about proportionate palliative sedation (PPS), the objective is to relieve suffering and medication is used continuously in the minimum amount needed to achieve this, being progressive increased if needed. On the other hand, PSU implies an intended reduction in consciousness (Twycross, 2019) and is used when patients find symptoms intolerable or wants to be in control. Medication is installed in a dosage to achieve unresponsiveness and remains until patient's death.…”
Section: Palliative Sedation To Unconsciousnessmentioning
confidence: 99%
“…"Continuous sedation until death at the patient's request is obviously different from palliative sedation" (Serey, 2019). Interpreting Twycross (2019), as the patient is unconscious, he cannot eat or drink by mouth, and this may lead to hasten death -biological life; also, PSU ends a person's ability to interact -biographical life. One may question whats is the difference between PSU and euthanasia.…”
Section: Palliative Sedation To Unconsciousnessmentioning
confidence: 99%
See 1 more Smart Citation